2005
DOI: 10.1007/s00027-004-0719-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and three-dimensional simulations of flow in a shallow reservoir subject to small-scale wind field inhomogeneities induced by sheltering

Abstract: Spremberg Reservoir is a small and shallow water body where wind sheltering along steep and densely vegetated sections of the shoreline is expected to produce small-scale inhomogeneities of the wind field across the water surface. The potential impacts of these inhomogeneities on the quasi-steady circulation in the main subbasin of the reservoir are investigated in this study by means of a three-dimensional hydrodynamic model. ADCP measurement profiles at three locations are available for comparison. Agreement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…The spatial variability of the wind stress influences strongly these motions. By studying the horizontal vorticity balance of the surface layer in Lake Kinneret and in Spremberg Reservoir, Laval et al (2003) and Rubbert and Köngeter (2005), respectively, showed that wind stress curl is a significant source of large scale horizontal vorticity with a magnitude comparable to that of the topographical curl [1,2]. Considering the spatial variability of the wind forcing they achieved improvements in simulated long wave amplitudes, phases and velocity fields.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial variability of the wind stress influences strongly these motions. By studying the horizontal vorticity balance of the surface layer in Lake Kinneret and in Spremberg Reservoir, Laval et al (2003) and Rubbert and Köngeter (2005), respectively, showed that wind stress curl is a significant source of large scale horizontal vorticity with a magnitude comparable to that of the topographical curl [1,2]. Considering the spatial variability of the wind forcing they achieved improvements in simulated long wave amplitudes, phases and velocity fields.…”
Section: Introductionmentioning
confidence: 99%
“…Such a decrease in the wind velocity can weak the setup and vertical circulation as in Imja. The wind field inhomogeneity over a lake made up by the surrounding topography directly impacts the hydrodynamics (Endoh et al, 1995, Laval et al, 2003, Rubbert and Köngeter, 2005.…”
mentioning
confidence: 99%
“…This causes a severe underestimation of the influence of wind on circulations under strong interacting conditions between the wind and the riverine current, e.g., for the low winds common to basins in lowland areas (Fenocchi et al, 2016). Use of 3D models, as in Rubbert and Köngeter (2005) and Anderson et al (2010), is therefore advised for these basins, also as simulation times are nowadays adequate (Fenocchi et al, 2016).…”
Section: Hydrodynamic Modelmentioning
confidence: 99%
“…Well-mixed conditions along the water depth were assumed, as verified by field measurements (Fenocchi, 2015). In fluvial lakes, the through-flowing current provides a background turbulence, preventing stratification even under no-wind conditions, so that baroclinic effects Rueda et al, 2003) can be neglected (Rubbert and Köngeter, 2005;Anderson et al, 2010;Schimmelpfennig et al, 2012). Indeed, small temperature gradients may be present in the deepest parts during summer drought periods.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation